Machine Learning for Fuel Consumption Prediction and Driving Profile Classification Based On Eco Data - S.Mohammed Ali; C.Yamini (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In recent years, predicting fuel consumption in real-time and classifying driving profiles have become increasingly important, especially when it comes to improving vehicle efficiency and promoting environmental sustainability. This project is all about using machine learning algorithms to forecast fuel consumption and categorize driving styles based on data from the Engine Control Unit. The current system relies on methods like XGBoost, Support Vector Regression,and Ridge Regression. However, our proposed system aims to boost accuracy in predictions and classifications by adding Random Forest, Logistic Regression, and Adaboost algorithms into the mix. We categorize driving profiles into five unique classes: Sporty, Eco, Calm, Normal, and Aggressive, all based on how fuel is consumed. This method not only sheds light on driving habits but also helps in crafting adaptive driving strategies and fuel-saving initiatives
Keywords: Machine Learning; Fuel Consumption; Driving Profile Classification; ECU Data; XGBoost; SVR; Ridge Regression; Random Forest; Logistic Regression; Adaboost